Zasady wydawania ksiąg ziemskich. Transliteracja = Principles of publishing of the land books. - Trawińska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The principles of transliteration of Latin-Polish court books presented in the article summarize many years of work aimed at editing the two oldest manuscripts from 1386-1400 and 1400-1407. The formulated rules provide for equal treatment of Latin and Polish entries. In accordance with the original, capital and lowercase letters, combined and separate spellings and punctuation will be rendered. All abreviations after reading will be marked accordingly.
Keywords: łacina średniowieczna; język staropolski; rękopis; 16 w.; medieval Latin; Old Polish language; manuscript; 16th century